2019
DOI: 10.21203/rs.2.337/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical analysis of microbiologically proven fungal keratitis according to prior topical steroid use: A retrospective study in South Korea

Abstract: Background: To compare the clinical characteristics and treatment outcomes of microbiologically proven fungal keratitis between users and non-users of prior topical steroids (PS and NPS, respectively) Methods: Eighty-three cases with microbiologically proven fungal keratitis between January 2000 and December 2016 retrospectively. Diagnosis of fungal keratitis was made through potassium hydroxide smear, culture, PCR, or biopsy. Baseline epidemiology, predisposing factors, clinical characteristics, microbiolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Lalitha et al [29] reported that the presence of hypopyon was a signifcant predictor of treatment failure in fungal keratitis. Cho and Lee [30] stated signifcant risk factors for treatment failure were hypopyon and deep infltration in microbiologically proven fungal keratitis. In this study about Fusarium keratitis, deep corneal infltration and hypopyon were signifcant in univariate logistic regression analysis, but their efects were attenuated in multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lalitha et al [29] reported that the presence of hypopyon was a signifcant predictor of treatment failure in fungal keratitis. Cho and Lee [30] stated signifcant risk factors for treatment failure were hypopyon and deep infltration in microbiologically proven fungal keratitis. In this study about Fusarium keratitis, deep corneal infltration and hypopyon were signifcant in univariate logistic regression analysis, but their efects were attenuated in multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that topical corticosteroids are not only risk factors for the causation of fungal keratitis, 5,6 but also worsen the clinical course of fungal infection. [7][8][9][10] Because topical or systemic antifungal drugs do not achieve fungicidal concentrations within the cornea, concurrent treatment with topical corticosteroids aggravates fungal keratitis because of unbridled proliferation of fungi. 9,11,12 Conventionally, topical corticosteroids are advised few weeks after TPK when the risk is low, but by this time, many grafts fail.…”
mentioning
confidence: 99%